Clearwater Project Public Hearing - Alley, Nathan; Kraus, Karen; Polefka, Shiva; Environmental Defense Center (Environmental Defense Center)
Three testimonies of reasons against Clearwater Port LNG Project by Center Nathan Alley, Shiva Polefka, and Karen Kraus, members of the Environmental Defense organization.